Proyek Pembuatan Sabun dari Minyak Jelantah untuk Pembelajaran Kimia SMA: Analisis Konten Kualitatif - Desrika Putri; Asep Supriatna; Triannisa Rahmawati (Postgraduate, University of Mataram, 2024)
Waste Cooking Oil (WCO) is one of hazardous waste causes serious issues, including environmental and health issues. WCO can be utilized in several bioproducts to reduce the potential of its problems. The purpose of this study is to create teaching-learning sequences from the context of utilization of waste cooking oil into soap. The teaching-learning sequences can be used as a basis to construct lesson design or teaching materials with project-based learning model. This is in line with curriculum in Indonesia known as “Kurikulum Merdeka” for a program called “Projek Penguatan Profil Pelajar Pancasila (P5)”. This research used Qualitative Content Analysis as a method with four stages including material collection, descriptive analysis, category selection, and material evaluation. Data were collected through fourteen literatures analysis and expert validation. Validation experts are from an experienced chemistry teacher and two lecturers from chemistry education field. Validation results the teaching-learning sequences’ is suitable for use for learning activity in terms of content. The result of this study is a teaching-learning sequences which divided into four sections including: (A) The Phenomenon of Waste Cooking Oil, (B) The Composition of Waste Cooking Oil and The Utilization of Waste Cooking Oil, (C) The Soap Making Process with WCO, and (D) The Benefit of WCO Utilization into Soap.